Spinoza’s Theological-Political Treatise in Iran - Reza Najafzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article is dedicated to the evaluation of Spinoza’s TTP. TTP is one of the most valuable treatises of the Enlightenment and represents the controversy of the old and the new in seventeenth-century Europe. The treatise includes the historical hermeneutics of Scripture and represents Spinoza’s republican political philosophy. The theological chapters of TTP, as well as its political chapters, contain topics that can be useful to the Iranian society involved in religious politics and political religion. Spinozist studies in Iran have not been significant compared to Anglo-Saxon, Jewish, and French traditions. These studies in the form of authorship and translation have become more serious from 2010 onward. The translation of TTP by Ali Ferdowsi in Iran is a good endeavor in itself, but there are also criticisms. For several reasons, Ferdowsi’s translation cannot be considered the end of the road: abstruse and unfamiliar language, unequal equivalents, misplacement of some sentences and words, and especially exclusive reliance on Silverthorne-Israel translation and lack of direct reference to Latin and other versions of this treatise can be enumerated as the pitfalls.